EFEKTIVITAS EKSTRAK DAUN SUREN (Toona sureni Merr.) DALAM PENGENDALIAN HAMA LALAT BUAH (Bactrocera dorsalis) PADA BUAH CABAI (Capsicum annuum L.) - Ida Hodiyah; Elya Hartini; Diana Safitri; Wawan Setiawan (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Bactrocera dorsalis is a very harmful pest for fruit and vegetable. Chemicalcontrol of these pests has raised another problem. The use of surian leaf extractcan be a good and environmentally friendly alternative control. This study aims to determine the effect of the administration of vegetable pesticides from suren leaf extract in the control of B. dorsalis on red chili. This research had been carried out at Siliwangi University and BBPOPT, Karawang in July to August 2019. This study used a Completely Randomized Design (CRD) with six replications. The concentration of suren leaf extract were : 0%, 0.025%, 0.05%, and 0.1%. The results showed that chili fruit extracts with the highest 0.1% consistently could reduce the number of larvae and the number of fruit attacked. The maincompounds contained in the surian leaf extract include 9,12-Octadecadienoic acid (Z, Z) -, phytol, acetate, phenol, 2-methyl-5- (1,2,2-trimethylcyclopentyl) -, (S) -, Cedren-13-ol, 8-, and 3,7,11,15-Tetramethyl-2-. These compounds were thought to be strong compounds that play a role in suppressing the number of larvae and the number of fruit attacked.